PARTIAL SLIP EFFECT OF Cu,Au,TiO2-NANO PARTICLE IN STUDY BIO MAGNETIC MAXWELL FLUID FLOW AND HEAT TRANSFER OVER A STRETCHING SHEET IN THA PRESENCE OF MAGNETIC DIPOLE - Murthy, Channakeshava; P T, Manjunatha; T, Lokesh (ShodhKosh: Journal of Visual and Performing Arts, 2022)
In this paper, we analyzed the Bio magnetic Maxwell fluid flow and heat transfer in a Nano fluid over a stretching sheet in the presence of magnetic dipole. The effects of velocity slip are considered in this study. Three different types of Nano fluids, namely the Copper-blood, the Gold- blood and titanium dioxide-blood are considered. The governing partial differential equations are transformed into ordinary differential equations using suitable transformation. Numerical solutions of these equations are obtained by using maple software. Inside the boundary layer, the variations of velocity, temperature various values of the appearing parameter, namely the ferromagnetic parameter, viscous dissipation parameter ,dimensionless distance, dimensionless curie temperature, Deborah number ,slip parameter are presented graphically and discussed in detail. The obtained results show that Gold has higher rate of heat transfer compared to Copper and Titanium dioxide. A good agreement is found between the present numerical results and the available results in the literature in some specific cases.